A systematic review of web-based learning in enhancing visualization skill - Ali, Dayana Farzeeha; Ahmad, Aimi Ruzaini; Othman, Nur Fadzilah; Jumaat, Nurul Farhana; Abd Wahab, Nuruljannah; Sundari, Riris Setyo (Semarak Ilmu Publishing, 2025)
In the digital era, visualization skills are critical for academic and professional success. This systematic review examines how web-based learning enhances these skills across various disciplines. This study focuses on addressing the challenges of developing effective visualization capabilities and the role of web-based learning in providing innovative solutions. This research utilized the PRISMA methodology to identify primary data utilizing specific keywords. Through extensive searches on Scopus, Web of Science, and ProQuest, 40 relevant studies were identified. The findings are organized into three themes: (1) Learning Innovations, (2) Digital Visual Education, and (3) Creative Visual Pedagogy. Results highlight web-based learning as a pivotal strategy in applied science and technology education, emphasizing collaborative and interactive technologies in enhancing spatial visualization and contributing to advanced educational practices.